Maternal high fat diets: impacts on offspring obesity and epigenetic hypothalamic programming - Harmancıoğlu, Begüm; Kabaran, Seray (Frontiers in Genetics, 2023)
It was determined that a maternal high-fat diet (HFD) during pregnancy is associated with rapid weight gain and fetal fat mass increase at an early stage. Also, HFD during pregnancy can cause the activation of proinflammatory cytokines. Maternal insulin resistance and inflammation lead to increased adipose tissue lipolysis and increased free fatty acid (FFA) uptake Maternal HFD during pregnancy (˃%35 calories from fat) lead to a significant increase in FFA levels in the fetus. However, both maternal insulin resistance and HFD have adverse effects on adiposity in early life. As a result of these metabolic alterations, excess fetal lipid exposure may affect fetal growth and development. Increases in inflammation and blood lipids can have detrimental effects on the development of the liver, adipose tissue, brain, skeletal muscle, and pancreas, increasing the risk for metabolic disorders. In addition, it was found that maternal HFD is associated with changes in the hypothalamic regulation of body weight and energy homeostasis by altering the expression of the leptin receptor, POMC, and neuropeptide Y in offspring. In addition, maternal HFDs alter methylation and gene expression of dopamine and opioid-related genes which cause changes in feeding behavior. All of these maternal metabolic and epigenetic changes may contribute to the childhood obesity epidemic through fetal metabolic programming. Dietary interventions are the most effective type of intervention during pregnancy to improve the maternal metabolic environment. Appropriate nutritional intake during pregnancy should be the principal goal in reducing the risks of obesity and metabolic disorders. In addition, dietary fat should be limited to <35% of energy, together with appropriate fatty acid intake during the gestation period.